Theatre and auditorium in Poitiers (2000–2008) - Sequeira, M. (Flashback: Carrilho da Graça, 2022)
The Theatre and Auditorium in Poitiers is located on the edge of the city’s historic centre, next to a slope that descends precipitously towards the high-speed railway line and train station. Within the continuity of the pre-existing urban fabric, the parallelepiped volumes and crystalline appearance of the theatre and auditorium rise up from a limestone foundation that forms a public terrace with a visual domain over the landscape of the Boivre river valley. The facades of the two volumes are equipped with a system that allows not only the projection of works of art conceived specifically for this purpose but also the dissemination of the events programme. In this manner, an interaction with the city and with the building’s mise en scene is established, the building is mediatised and its constant transfiguration is made possible. While an intense visuality characterises the exteriors of the two volumes, it is their acoustic qualities that prevail inside — in the theatre, which seats around 700 and hosts an informal and multi-purpose programme, a balance has been sought between the technical requirements of the stage machinery and the audience’s comfort, while in the auditorium, which has a capacity of around 1,000, a quadratic difusion system redistributes the sound in a homogeneous way, so that the music reaches the entire audience simultaneously and without any loss of energy.